Capacity Building of Teachers on Learning Outcomes: Back to Basics a panacea for Kendriya Vidalaya teachers to enhance the learning outcomes of students - Gupta, Nirmala (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Back to basic is an ingenuity taken up by the KendriyaVidalaya Sangathan for the capacity building of both the teachers and the students. A random check was piloted and establishes that students answered all the question without understanding the basic skill and concept. Rote learning was precisely prevalent amongst students. Teaching lacked variety as it emphasized much on completion of syllabus.In order to make them understand the basic skills this conception was introduced by the KVS because students were lacking the 21st century skills. In order to brand them as autonomous learners, and imbibe the perception of learning to learn”Back to Basic” was introduced. Bridging the gap that young scholars are often left with, especially after passing Kendriya Vidyalaya Sangathan (KVS) students across the country will soon be able to benefit from the Back to Basics programme that seeks to brush-up the lessons that children have not been able to absolutely understand. Teachers will now have to safeguard the basic foundation from the previous class that is reinforced for each student. An initiative to certify attainment of expected learning outcomes mentioned in the NCERT document from classes I to VIII in all subjects. This Project aims to pledge dictate of the RTE Act and fill the gaps in learning confirming class /age appropriate learning capability of children with special emphasis on basic numeracy and reading competencies.